Optical spectra and luminescence kinetics of the Sm3+ and Yb3+ centres in the lithium tetraborate glasses - Padlyak, Bohdan; Ryba-Romanowski, Witold; Lisiecki, Radosław; Adamiv, Volodymyr; Burak, Yaroslav; Teslyuk, Ihor; Banaszak-Piechowska, Agnieszka (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Optical absorption, luminescence excitation, and emission spectra as well as luminescence kinetics of the Sm- and Yb-doped glasses with lithium tetraborate (Li2B4O7) composition were investigated and analysed. The Sm- and Yb-doped lithium tetraborate glasses of high optical quality were obtained in air from corresponding polycrystalline compounds according to standard glass synthesis technology. The Sm and Yb impurities were added to the Li2B4O7 compound in the form of Sm2O3 and Yb2O3 oxides in amount of 0.4 mol%. Using optical and electron paramagnetic resonance spectroscopy it was shown that the Sm and Yb impurities are incorporated into the lithium tetraborate glass network as Sm3+ (4f5, 6H5/2) and Yb3+ (4f13, 2F7/2) ions, exclusively. All of the observed transitions in the absorption and luminescence spectra of Sm3+ and Yb3+ centres were identified. The luminescence kinetics of the Sm3+ and Yb3+ centres in the Li2B4O7 glass are characterised by a single exponential decay. Decay constants for the main emission transitions of the Sm3+ and Yb3+ centres in the lithium tetraborate glass were obtained at T = 300 K. Incorporation peculiarities and optical spectra of Sm3+ and Yb3+ ions in the lithium tetraborate glass have been discussed in comparison with other borate glasses and crystals.
Optica Applicata, Vol. 40, 2010, nr 2, s. 427-438
Keywords: optyka; borate glasses; Sm3+ centre; Yb3+ centre; optical absorption; luminescence; decay kinetics; local structure